Dampak Teknologi Komunikasi Terhadap Komunikasi Keluarga - Suryani, Irma; Fatiha, Putri Amana; Salsa, Nabila Husna; Rizqiah, Nabilah; Rahmadani, Siti; Sari, Vika; Hakiki, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This article discusses the impact of communication technology on family interactions using the literature study method. The research analyzes various sources to understand how technological advances, such as instant messaging apps and video calls, affect family communication dynamics. The results show that communication technology can increase the frequency and quality of interactions, allowing family members to stay connected despite being separated by geographical distance. However, on the other hand, excessive use of technology can reduce the quality of face-to-face communication, which is important for building emotional closeness. In addition, generational differences in technology utilization often create communication gaps that can potentially trigger conflict. Therefore, this article emphasizes the importance of balance in the use of technology to maintain harmony and meaning of communication in families in the digital era.